Secure Crypto currency Transaction using Elliptic Curve Digital Signature Algorithm for Storing Wallets - Dhilipkumar.S (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Crypto currency has become a universal currency. Though certain countries restrict its usage and plans to create their own crypto currency, the prevalence of the existing crypto currencies such as Bitcoin and their values are remarkable. Crypto currencies along with blockchain technology enables the anonymity of users, decentralization but with security and reliability. The security of encrypted wallets is becoming increasingly important as the overall value of digital currency increases. The hardware only wallets are secure somehow but it is not likely to have convenience of software-based wallets. Similarly, the software wallets are handy but have cyber vulnerabilities. In this paper, a hardware based crypto wallet for storage and transaction purposes is proposed by using encryption techniques. The main objective is to build a safe, secure, and durable wallet for storing the crypto currency and to maintain a ledger of the transactions which in turn increases the wallet’s security and the convenience of using it for an average consumer. The remote access will be available when the wallet is online. Hence for authentication, we are using Elliptic Curve Digital Signature Algorithm (ECDSA). The authenticity of the data and credibility of user’s credential can be proved with this technique.